2021
DOI: 10.1101/2021.08.31.458313
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetic activators of apoptosis, necroptosis and pyroptosis for probing cell death dynamics and bystander cell responses

Abstract: Targeted and specific induction of cell death in individual or groups of cells holds the potential for new insights into the response of tissues or organisms to different forms of death. Here we report the development of optogenetically-controlled cell death effectors (optoCDEs), a novel class of optogenetic tools that enables light-mediated induction of three types of programmed cell death (PCD), apoptosis, pyroptosis and necroptosis, using Arabidopsis thaliana photosensitive protein Cryptochrome2. OptoCDEs e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Having established a leading role for BM engulfments in neuronal removal we used live reporters for microtubules (Tg ( UAS:EMTB-3xGFP );) and F-actin (Tg( UAS:mNG-UtrCH ); Shkarina et al, 2021), to determine the nature and dynamics of these extensions. We found that microglia have different types of extensions (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having established a leading role for BM engulfments in neuronal removal we used live reporters for microtubules (Tg ( UAS:EMTB-3xGFP );) and F-actin (Tg( UAS:mNG-UtrCH ); Shkarina et al, 2021), to determine the nature and dynamics of these extensions. We found that microglia have different types of extensions (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Transgenic marker 6xUAS:lyn-tagRFPt p5E_6xUAS pME_lyn p3E_tagRFPt cry:ECFP 6xUAS:mNeonGreen-Rab5a p5E_6xUAS pME_mNeonGreen (Shkarina et al, 2021) p3E_Rab5 (Hartmann et al, 2020) cmlc2:tagRFP 6xUAS:Lamp1-mGFP p5E_6xUAS pME_Lamp1-mGFP p3E_polyA cmlc2:tagRFP 6xUAS:miRFP670-cetn4 p5E_6xUAS pME_miRFP670 p3E_cetn4 (Revenu et al, 2014) cry:mKate2…”
Section: Final Vector P5e Vector Pme Vector P3e Vectormentioning
confidence: 99%
“…In mammals, the latter protein is cleaved by Caspase-1 downstream of the classical inflammasome cascade and IL-1 secretion [ 46 ]. Nevertheless, zebrafish Caspa and Caspb proteins are able to in vitro cleave the human GSDMD [ 47 ] and zebrafish Gasdermin E [ 22 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there is a need for vesicle markers to trace the intracellular trafficking of mycobacteria and for fluorescently tagged proteins to study the activation of innate immunity signaling mechanisms in real time. Novel optogenetic tools are now being applied in zebrafish disease models and this technology opens new possibilities also for infection research, enabling local and timed activation of factors at the host‐pathogen interface (Asakawa et al., 2021 ; Formella et al., 2018 ; Shkarina et al., 2021 ). These and other technological advances will maximize the use of zebrafish as a model host and will drive research into the mechanisms of innate host defense and pathogen evasion strategies, the necessary basis for therapeutic innovations.…”
Section: Discussionmentioning
confidence: 99%